Do financial development, urbanization, economic growth and renewable energy promote the emission mitigation agenda of Africa? Evidence from models that account for cross-sectional dependence and slope heterogeneity - Kong, Yusheng; Donkor, Mary; Jin, Cheng; Musah, Mohammed; Nkyi, Joseph Akwasi (Frontiers in Environmental Science, 2024)
Carbon emissions from anthropogenic human activities are viewed as the major cause of pollution in the environment. The Paris Treaty came into effect to help minimize the galloping rate of global ecological pollution.But, despite nations committing to the guidelines of this accord, ecological contamination continues to rise. To help curb the above menace, a study on the connection between financial development, urbanization, economic growth, renewable energy consumption, and environmental sustainability of selected African countries over the period 1990 to 2019 was deemed appropriate. In attaining this goal, econometric techniques that are robust to heterogeneity and residual cross-sectional dependence were deemed appropriate. From the preliminary analysis, the panel was heterogeneous and cross-sectionally dependent. Also, all the series were stationary after first difference and cointegrated in the long-run. The dynamic common correlated effects mean group (DCCEMG), and the common correlated effects mean group (CCEMG) estimators were engaged to explore the elasticities of the predictors, and from the results, renewable energy consumption (RNE) reduced carbon emissions (CE) in North and East Africa. In contrast, economic growth (GDP) and urbanization (UBN) promoted CE. Besides, financial development (FD) in the CCEMG estimation exhibited a negative and substantial influence in North and East Africa. Though, FD had a negative connection with CE in the South, its effect was statistically insignificant. For the DCCEMG results, only North Africa had a significant and a reducing effect of FD on CE. The elasticities of the other determinants were heterogeneous across the various panels. Summarily, FD, RNE, GDP, and UBN significantly predicted CE in the aggregate panel. But there was heterogeneity in the coefficients across the sub-panels. Policy recommendation to help advance the carbon-neutrality target of the region were proposed.